2004
DOI: 10.1016/s0035-9203(03)00003-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and side effects of praziquantel against Schistosoma mansoni in a community of western Côte d’Ivoire

Abstract: keywords Schistosoma mansoni, praziquantel, resistance correspondence Y.S. Liang, Jiangsu Institute of Parasitic Diseases, Meiyuan, Wuxi, Jiangsu 214064, P. R. China. The tolerance of Schistosoma mansoni to praziquantel has been reported in some endemic regions (Fallon et al. 1995; Stelma et al. 1995; Ismail et al. 1996; Guisse et al. 1997). To establish the reasons for clinical failures of praziquantel, a simple, quick and economic assay is required to detect resistance. Ideally this will involve the use of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 35 publications
11
67
3
1
Order By: Relevance
“…Accordingly, infected children younger than 10 years and in the 10-14 age group showed high percent of heavy and moderate infection and low cure rate after treatment as compared to those in the [15][16][17][18][19][20][21][22] age group. This agrees with similar previous studies [16,36,43] in which significant association between classes of intensity and age groups was observed. The present study area is an area of intense transmission where school age children acquire heavy infection.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Accordingly, infected children younger than 10 years and in the 10-14 age group showed high percent of heavy and moderate infection and low cure rate after treatment as compared to those in the [15][16][17][18][19][20][21][22] age group. This agrees with similar previous studies [16,36,43] in which significant association between classes of intensity and age groups was observed. The present study area is an area of intense transmission where school age children acquire heavy infection.…”
Section: Discussionsupporting
confidence: 94%
“…These values are in general within the usual cure rate ranges (63-95%) of PZQ against S. mansoni reported in different epidemiological settings [4,[26][27][28] . Some previous studies have reported efficacy higher than 85% for PZQ [29][30][31][32][33][34] , while others have reported lower (<63%) efficacy for the drug [13][14][15][16][17][18][19][20][21]35,36] . Such variations might be attributable to differences in the number of treatment, factors related to the host, parasite, and drugs or to the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated that praziquantel is a safe and efficacious treatment against both species, and that repeated chemotherapy decreases infection and related morbidity. [1][2][3][4][5][6][7] One of the main control methods is treating schoolchildren with praziquantel together with albendazole as part of school health programmes. As this method uses the existing school infrastructure and provides easy accessibility to children, it is a cost-effective public health strategy, 8 and many pilot programmes have demonstrated its feasibility, affordability and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the overall effect estimates as reported in this review may be lower than studies including all-age subjects, as adults usually show lower infection intensities than school-aged children and, conversely, higher treatment efficacies. This issue has been documented for S. mansoni (Raso et al 2004), and it is conceivable that the same holds for S. haematobium. It should also be noted that restricting treatment to school-aged children leaves untreated adults and pre-school children still excreting eggs to maintain transmission, if indeed transmission is a function of egg output.…”
Section: Study Population Issuesmentioning
confidence: 76%